Building performance and end-user interaction in passive solar and low energy housing developments in Scotland. (3rd September 2018) - Sharpe, Tim; McGill, Gráinne; Menon, Rosalie; Farren, Paul
ABSTRACT: In the UK housing sector, changes to building regulations have raised standards for fabric performance, bringing about a demand for affordable, low energy housing. Housing Associations have been at the forefront of adopting these measures, but as owners of long term rented stock it is important for them to understand and evaluate the performance of both 'as-built' and 'as-occupied' dwellings. This paper describes a detailed evaluation of three new-build social housing demonstration projects located in Glasgow (Scotland). The study included occupant surveys in each scheme, fabric testing and detailed monitoring of environmental conditions, energy consumption, and evaluation of occupancy behaviours in eight dwellings. A particular focus of this paper is the ventilation performance as the homes are ventilated differently using natural, mechanical extract and mechanical heat recovery methods. The results showed a wide discrepancy of energy consumption and poor levels of ventilation, particularly in bedrooms. Causes of this included the design and installation of the ventilation provision but occupant interaction with the systems was also a significant factor. Two sites included sun-spaces that, despite having good potential for preheat ventilation and drying spaces, were underperforming. The study highlights significant impacts of the complex interactions between heating and ventilation systems, and the apparent need for more effective ventilation strategies and systems in bedroom spaces, but also improved strategies for end-user understanding of, and interaction with, both mechanical systems and natural ventilation opportunities. The papers aims to provide robust and credible evidence on which to base critical regulatory and design decisions on the most effective means of ventilating low carbon social housing in Britain.